Controlled processing during sequencing - Thothathiri, Malathi; Rattinger, Michelle (Frontiers in Human Neuroscience, 2015)
Longstanding evidence has identified a role for the frontal cortex in sequencing within both linguistic and non-linguistic domains. More recently, neuropsychological studies have suggested a specific role for the left premotor-prefrontal junction (BA 44/6) in selection between competing alternatives during sequencing. In this study, we used neuroimaging with healthy adults to confirm and extend knowledge about the neural correlates of sequencing. Participants reproduced visually presented sequences of syllables and words using manual button presses. Items in the sequence were presented either consecutively or concurrently. Concurrent presentation is known to trigger the planning of multiple responses, which might compete with one another. Therefore, we hypothesized that regions involved in controlled processing would show greater recruitment during the concurrent than the consecutive condition. Whole-brain analysis showed concurrent > consecutive activation in sensory, motor and somatosensory cortices and notably also in rostral-dorsal anterior cingulate cortex (ACC). Region of interest analyses showed increased activation within left BA 44/6 and correlation between this region’s activation and behavioral response times. Functional connectivity analysis revealed increased connectivity between left BA 44/6 and the posterior lobe of the cerebellum during the concurrent than the consecutive condition. These results corroborate recent evidence and demonstrate the involvement of BA 44/6 and other control regions when ordering co-activated representations.